Effect of magnetic trajectories in a magnetically coupled dual stator five phase PMSG - Kumar R.R.; Singh S.K.; Srivastava R.K. (My University, 2025)
Emergence of renewable power utilities led to the advancement of high power density generators. Permanent magnet generators are being considered as a good solution for this. The prime focus of this paper is to analyze the role of leakage flux in surface mounted magnetically coupled cascaded dual stator five phase permanent magnet synchronous generator. Analysis and modeling of leakage flux for this machine is done, which shows its affect on air gap flux density, that could introduce harmonics in the generated voltage. Air gap fluxes and leakage parameters are derived in terms of generator dimensions and its magnetic properties. Leakage flux, by accurate prediction of flux distribution along various magnetic trajectories, plays a vital role in the design of Permanent magnet generator. Finite element method (FEM) is adopted to validate the results of proposed analytical model. Both results are very close and deviation of results is around 3%, that suggests the significance of including leakage flux for analytical modeling, which would further speed up the optimal design process of the machine. © 2015 IEEE.